LEGAL STRENGTH OF POWER OF ATTORNEY OF IMPOSING GUARANTEE RIGHTS REGARDING THE ISSUANCE OF REGULATION OF THE HEAD OF THE NATIONAL LAND AGENCY NUMBER 8 OF 2012 - Ni Putu Sawitri Nandari; Ketut Elly Sutrisni; Wayan Suderana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The Power of Attorney for Imposing Mortgage is a special power of attorney, does not contain the power to take other legal actions other than imposing Mortgage as stipulated in chapter 15 of Law no. 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land (UUHT). Notary as a Public Official who is authorized to make authentic deeds is also authorized to make a Power of Attorney to impose Mortgage in accordance with the provisions stipulated in Law Number 2 of 2014 concerning the Position of Notary (UUJN). However, in its development the process of making a Power of Attorney for Imposing Mortgage by a Notary experienced obstacles which became a problem in writing this thesis which was related to the Regulation of the Head of the National Land Agency Number 8 of 2012 concerning Amendments to the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning provisions for the Implementation of Government Regulation Number 24 of 1997 concerning Land Registration. This research is a normative research, namely by looking for legal materials based on library research. Legal materials obtained from library research will be analyzed using a qualitative descriptive method. The type of approach used is the legal concept analysis approach and the approach through laws and regulations. The results of the study show that the Power of Attorney for Imposing Mortgage made by a Notary after the issuance of Regulation of the Head of the National Land Agency Number 8 of 2012 has permanent legal force. Notaries have their own legal umbrella within their authority to make a Power of Attorney to impose Mortgage as stipulated in UUJN. Therefore, the provisions contained in the Regulation of the Head of the National Land Agency Number 8 of 2012 cannot be applied to Notaries.